Hubungan Faktor Sosial Petani dengan Penerapan Teknologi Budidaya Padi Hibrida di Kecamatan Pulung Kabupaten Ponorogo - SAPUTRI, DESYTA YUVITASARI; SUARDI, I DEWA PUTU OKA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
The Relationship of Social Factors of Farmers with Application of Hybrid Rice Cultivation Technology in Pulung Sub-Distrct of Ponorogo Regency Hybrid rice is a new innovation in agriculture. In its development as an innovation in agriculture, farmers must understand first about how to cultivate hybrid rice because sometimes farmers do not understand how to cultivate hybrid rice properly and correctly. The process of understanding in the implementation of a new innovation by farmers in farming depends on the social factors. This study aims to identify the level of social factors of farmers, to identify the level of application of hybrid rice cultivation technology, and to find out the relationship between social factors with the application of hybrid rice cultivation technology in the Sub-District Pulung of Ponorogo Regency. Sampling was conducted by saturated sampling method. Data analysis method used is descriptive analysis and rank spearman correlation analysis. The result of descriptive analysis shows that the level of social factor of farmers was in the low category with the achievement score of 1.56, while the application level of hybrid rice cultivation technology in Pulung Sub-District was in the medium category with achievement score of 1.96. The result of correlation analysis showed a strong relationship between the social factors with the application of hybrid rice cultivation technology by the correlation value of 0.837 ** positive direction of the confidence level at 99%. This means that the higher the level of social factors of farmers, the higher the application level of hybrid rice cultivation technology.